PT DYANDRA PROMOSINDO SEBAGAI MITRA PEMERINTAH DALAM INDUSTRI MEETING, INCENTIVE, CONVENTION, EXHIBITION (MICE) - Permadi, Daffa Saskoro; Erviantono, Tedi; Erawan, I Ketut Putra (Jurnal Nawala Politika, 2023)
MICE (Meeting, Incentive, Conference, Exhibition) or known as convention tourism is part of the tourism industry which aims to attract both foreign and domestic tourists to carry out tourism activities in Indonesia. PT Dyandra Promosindo as one of the largest MICE business actors in Indonesia plays an important role in the advancement of the MICE industry and also works together with the government in the growth of tourism in Indonesia. In this article, the researcher uses the associative research method which is obtained in the form of sentences and observations. This research focuses on the mutual relationship between the two parties studied, namely PT Dyandra Promosindo and the government, as well as the impact of this collaboration on the wider community. The results of the analysis show that PT Dyandra Promosindo plays an active role in efforts to advance Indonesian tourism and fully supports government programs through events organized by PT Dyandra Promosindo, as well as mutual relations between PT Dyandra Promosindo and the government.   Keywords : Collaboration, Events, Government, Industry, MICE, Mutual, Tourism,